Sociological approach on the changes of the death penalty to Drug Criminals - Abdolreza javan jafari; Muhammad Saleh Esfandiari Bahraseman (Faṣlnāmah-i Pizhūhish-i Huqūq-i Kiyfarī, 2019)
In the present study, regardless of the Penological and philosophical aspects, the effect of sociological changes and factors on the increasing of death penalty, as well as, its reduction in relation to Drug crimes were studied. In this regard, a question titled "what are the main reasons of increasing the death penalty for some drug traffickers in early years of the revolution and during of the imposed war and executed in public by considering the "punishment and social solidarity" theory. In those times, death penalty have been as the emotional expression and reflection of community anger against violation of social values. However, death penalty has presented the most important function in those social situation. During the time, the attitude of people and elites towards the punishment and especially death penalty on drug crimes in terms of advection of socio-cultural evolutions and the change of values in the context of society was upgraded. One of the most important signs of mentioned evolution is the lack of execution of the death penalty in public.